Evaluation of Pontoon Facilities in supporting safe transportation - febriansyah, Febriansyah; Kadarsah, Edi; Latuheru, Paulina Mutiara (IWJ : Inland Waterways Journal, 2024)
The pontoon pier, which was built in 1984, originally functioned as a place to dock for speedboats. However, since 2017, the pier has been used to berth for larger ships. Unfortunately, the supporting facilities for the pontoon pier, such as fenders and bolders, have not been replaced, which could potentially cause damage to the pier. The analysis used quantitative methods by conducting surveys and direct observation in the field. Based on the results of the analysis, it is necessary to increase the type of fender to a cylindrical fender with dimensions of 300 mm x 150 mm or Type A Fender with the KAF 200 H type of 12 fenders and the addition of Bolders on the front pier to 4 for safety transport.